2018
DOI: 10.1002/cphc.201701125
|View full text |Cite
|
Sign up to set email alerts
|

Shortfall of B3LYP in Reproducing NMR JCH Couplings in Some Isomeric Epoxy Structures with Strong Stereoelectronic Effects: A Benchmark Study on DFT Functionals

Abstract: Unprecedented scatter plots of calculated versus measured NMR J coupling constants in six densely oxygen functionalized epoxides are found with some B3LYP protocols, an effect attributed to stereoelectronic effects. Hence, 26 other exchange-correlation density functionals (xc DFs) are benchmarked in this work. Very good results are achieved with mPW1PW91 and PBE0 in conjunction with the pcJ-1 basis set (BS) of moderate size. A thorough statistical analysis of 53 relationships between the predicted and observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 124 publications
(177 reference statements)
0
11
0
Order By: Relevance
“…DFT was then used to determine if the large 3 J CC coupling constants could be accurately predicted. Several different model chemistries were evaluated that have been previously shown to produce high‐quality coupling constant predictions . Most frequently, the B3LYP functional combined with moderately sized basis sets (e.g., triple‐zeta) has been utilized for n J HH and n J CH coupling constant predictions, but there are fewer reports on n J CC calculations .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…DFT was then used to determine if the large 3 J CC coupling constants could be accurately predicted. Several different model chemistries were evaluated that have been previously shown to produce high‐quality coupling constant predictions . Most frequently, the B3LYP functional combined with moderately sized basis sets (e.g., triple‐zeta) has been utilized for n J HH and n J CH coupling constant predictions, but there are fewer reports on n J CC calculations .…”
Section: Resultsmentioning
confidence: 99%
“…found B3LYP/EPR‐III predicted 27 1 J CC values for three bicyclic terpene natural products with a maximum deviation of 3.4 Hz (5%) . In a comprehensive benchmark study of 27 density functionals, Adamson and coworkers observed the highest accuracy (mean absolute deviation of 0.20 Hz) for the mPW1PW91 functional paired with the pcJ‐1 basis set for prediction of n J CH values for several epoxy compounds . Lastly, we also considered the B3PW91/6‐311++G(d,p) model chemistry employed by Bugaj et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations